Costs, Wages and Prices in the ’Libro de cuentas de Pedro Bluson y Juan Francisco Larumbe’, Huesca, 1625-1642: Price and Cost Analysis in a Printing House from the Spanish Golden Age - Pedraza Gracia, Manuel José (Revista General de Información y Documentación, 2020)
This work analyses the production costs of printing, the wages of the workers employed in the press and the selling prices of the products printed in Pedro Blusón’s and Juan Francisco Larumbe’s workshops in Huesca between 1625 and 1642, using as a source the oldest accounting book preserved in Spain, the Libro de cuentas de Pedro Blusón y Juan Francisco Larumbe (Archivo Histórico Provincial de Huesca, F. 48).